Evaluation of actual evapotranspiration of a Quercus ilex L. stand by the Bowen ratio-energy budget method - Pitacco, A; Gallinaro, N; Giulivo, C (Plant Ecology, 1992)
Actual evapotranspiration from a closed-canopy Quercus ilex L. stand has been estimated by applying the Bowen Ratio-Energy Budget method. Daily water loss was 3.5 mm day ~, with a peak rate near 0.6 mm hour ~. The phenomenon of thermal inversion, quite common in mediterranean climates, seemed to play a significant role in reducing evapotranspiration, by promoting dew formation and delaying the establishment of fluxes of latent and sensible heat away from the canopy. Dew, which may form over many hours in the night, appears to be a major sink of available energy in the early morning and may represent a useful water source for stressed foliage. The alternating processes of condensation and evaporation may have a beneficial effect on the closed stand micro-environment.
Keywords: actual evapotranspiration; bowen ratio; energy balance; Quercus ilex L